DEVELOPMENT OF A TRADITIONAL GAME-BASED INTERACTIVE E-BOOK TO IMPROVE LEARNING MOTIVATION AND LONG JUMP SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Barkah Suko Mulyono; Yudha Febrianta (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Long jump learning still faces challenges due to limited learning media and students’ mastery of movement techniques. This study aims to develop a traditional game-based interactive e-book to improve learning motivation and long jump skills among junior high school students. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research was conducted in Grade VII at SMP Negeri 2 Madukara, involving 22 students in the experimental group and 22 students in the control group. Data were collected through expert validation, learning motivation questionnaires, long jump skill tests, and documentation. Data analysis was performed using IBM SPSS Statistics 26 through validity, reliability, normality, homogeneity, Mann–Whitney U Test, and effect size analyses. The results showed that the traditional game-based interactive e-book was feasible for use, with media expert validation of 78.89% and material expert validation of 73.85%. The effectiveness test indicated significant differences between the experimental and control groups in learning motivation and long jump skills (p < 0.05), with a large effect size category. Therefore, the traditional game-based interactive e-book is effective in improving students’ learning motivation and long jump skills. Teachers are recommended to utilize interactive media based on traditional games to support more engaging and meaningful Physical Education learning